Videoteaching – a way to improve student experience - MACH, Petr; KROTKÝ, Jan (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The proposed research is focused on and maps the various methods of communication of students who study master teaching courses at Faculty of Education (or existing elementary and secondary teachers) in the pedagogical practice. The experience with the project will lead to improve the preparation of future teachers (student) and improve approach of the preparing teachers. Present educational system imposes high requirements on teachers of all levels. Personality development is marginalized in teacher training, mainly the development of creative abilities and skills to solve conceptual matters and dynamic changes in the educational process. One of the ways of improvement the personality and professional development is to include the case study method. Case study method of didactic situations is a modern procedure of effective development of professional abilities in future teachers.